2010
DOI: 10.1038/leu.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive alloimmune intervention in high-risk pediatric acute lymphoblastic leukemia patients guided by minimal residual disease level before stem cell transplantation

Abstract: Relapse of pediatric acute lymphoblastic leukemia (ALL) remains the main cause of treatment failure after allogeneic stem cell transplantation (alloSCT). A high level of minimal residual disease (MRD) before alloSCT has been shown to predict these relapses. Patients at risk might benefit from a preemptive alloimmune intervention. In this first prospective, MRD-guided intervention study, 48 patients were stratified according to pre-SCT MRD level. Eighteen children with MRD level X1 Â 10 À4 were eligible for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 52 publications
8
59
2
Order By: Relevance
“…30,31,36 In the first year posttransplant there is little tolerance for chemotherapy, and hardly any chance for cure without proceeding to another transplant, which is only beneficial in a low or preferably negative MRD state. 7,8,10,12,37 We have shown that blinatumomab administration was feasible and had impressive antileukemic activity against highly chemorefractory disease in our pediatric patients, as has already been shown for adult B-ALL. 31,36 Six of 9 patients achieved complete remission after blinatumomab treatment irrespective of leukemia burden prior to the start of therapy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…30,31,36 In the first year posttransplant there is little tolerance for chemotherapy, and hardly any chance for cure without proceeding to another transplant, which is only beneficial in a low or preferably negative MRD state. 7,8,10,12,37 We have shown that blinatumomab administration was feasible and had impressive antileukemic activity against highly chemorefractory disease in our pediatric patients, as has already been shown for adult B-ALL. 31,36 Six of 9 patients achieved complete remission after blinatumomab treatment irrespective of leukemia burden prior to the start of therapy.…”
Section: Discussionmentioning
confidence: 92%
“…[3][4][5][6] Level of pre-transplant minimal residual disease (MRD) has been shown to be an important adverse prognostic parameter for estimating the risk of relapse; MRD, therefore, influences long-term event-free survival after allogeneic stem cell transplantation. [7][8][9][10][11][12] In particular, patients who relapsed posttransplant have an extremely poor prognosis and need to achieve another hematologic remission or an even more advantageous very low or negative MRD level before proceeding to a subsequent SCT. 6 Additional chemotherapy will often be of limited benefit and may be associated with high toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The OS for adults with ALL who relapse after initial therapy is poor, with less than 10% 5-year OS and a median survival of 2-3 months (19,(24)(25)(26). To date, the most common relapse-reduction strategy after HSCT involves immune manipulation, ranging from donor lymphocyte infusion (DLI) to second HSCT (27)(28)(29). While graft-versus-host disease (GVHD) reduces relapse risk (30), conventional (not genetically modified) DLI provides minimal benefit in these patients, with remission rates below 10% and a high GVHD incidence (31,32).…”
Section: Cd28mentioning
confidence: 99%
“…86 This encouraging experience is contrasted by observations of more limited and largely temporary effects of such pre-emptive measures in acute leukemia, suggesting insufficiency to prevent overt relapse in many patients. 35,39,[87][88][89][90] Additional (pre-emptive) post-HCT therapy Useful additional post-HCT therapy could encompass conventional chemotherapies (ideally non-cross-resistant to those used for prior therapies), Ab-based therapeutics, epigenetic modifying drugs and/or molecularly targeted agents. Supporting this strategy, Platzbecker et al 91 observed that 16 out of 20 patients with CD34 þ AML or myelodysplastic syndromes who received the DNA methyltransferase I inhibitor, azacitidine, after they experienced a decrease in CD34 þ donor chimerisms to o80% responded with either increasing donor chimerism or stabilization thereof.…”
Section: Using Pre-hct Mrd To Tailor Therapy In Acute Leukemiamentioning
confidence: 99%